(untitled) (Herald of Journalism, 2018)
The article contains the results of a study on the internationalization of Turkestan in the diplomatic sphere and international relations. The author considers that the activity of governments in exile in the interwar period in the 20th century is socially significant and provided a high spiritual core of internationalization in the world community. This page of history is especially relevant in the context of the article by the President «A glance at the future: the modernization of public consciousness.» The purpose of the study is to study the stages of international recognition of Kazakhstan and Central Asia, to the world level. The idea of the study is to recreate the diplomatic activities of Mutafa Shokai, his like-minded people from Ukraine and the Caucasus. Applied value of the research is to teach the course «International Law and the Media». The scientific significance of the research topic lies in the discourse of the role of emigration in the global media space. The methodology of the research is based on the laws of dialectics and the basic principles of humanitarian research, the principle of historicism, verification of sources, analysis and synthesis, etc. The value of the research is measured by an updated methodological approach in the spiritual and moral evolution of politicians of the 20th century. Practical application of the results – new courses on the basis of the Institute for Advanced Studies of the University and mass open online courses (MOOK).